Pengaruh Permainan Acak Geometri Terhadap Perkembangan Kecerdasan Logika-Matematika Anak - Fajriati, Ruliana (JAPRA (Jurnal Pendidikan Raudhatul Athfal), 2020)
Based on the results of observations in the field on the development of mathematical logical intelligence in students has not developed optimally so it is necessary to apply the geometry random game media. This study aims to determine the effect of random geometry on the development of mathematical-logic intelligence in children at Nasyithatun Nisa Kindergarten, Teluk Kiambang, Tempuling District, Indragiri Hilir Regency. The sample used in this study was 13 students consisting of one class. The data collection techniques used are test, observation and documentation. The data analysis technique used the Prerequisite test and Hypothesis test using the SPSS 17. The research hypothesis was that the activity of using geometric random games had an influence on the development of mathematical-logic intelligence in group B children at Nasyithatun Nisa Kindergarten. This can be seen from the results of data analysis on the comparison of the pretest and posttest classes obtained by tcount = 50,229 and Sig. (2-tailed) = 0,000. because of Sig. (2-tailed) = 0,000 <0,05, it can be concluded that there is a significant effect after using geometric random play in learning. So that means Ho is rejected and Ha is accepted, which means that in this study there is the influence of random geometry games before and after treatment. The effect of random geometry on the development of logic-mathematical intelligence in children at Nasyithatun Nisa Kindergarten was 82,005%.